Preparation and characterization of nano-galvanic bimetallic Fe/Sn nanoparticles deposited on talc and its enhanced performance in Cr(VI) removal - Mitra Bayat (Nature Portfolio, 2021)
Abstract In this study, talc-supported nano-galvanic Sn doped nZVI (Talc-nZVI/Sn) bimetallic particles were successfully synthesized and utilized for Cr(VI) remediation. Talc-nZVI/Sn nanoparticles were characterized by FESEM, EDS, FTIR, XRD, zeta potential, and BET analysis. The findings verified the uniform dispersion of nZVI/Sn spherical nanoparticles on talc surface with a size of 30–200 nm, and highest specific surface area of 146.38 m2/g. The formation of numerous nano-galvanic cells between nZVI core and Sn shell enhanced the potential of bimetallic particles in Cr(VI) mitigation. Moreover, batch experiments were carried out to investigate optimum conditions for Cr(VI) elimination and total Cr(VI) removal was achieved in 20 min using Sn/Fe mass ratio of 6/1, the adsorbent dosage of 2 g/L, initial Cr(VI) concentration of 80 mg/L, at the acidic environment (pH = 5) and temperature of 303 K. Besides, co-existing of metallic cations turned out to facilitate the electron transfer from the nano-galvanic couple of NZVI/Sn, and suggested the revolution of bimetallic particles to trimetallic composites. The aging study of the nanocomposite confirmed its constant high activity during 60 days. The removal reaction was well described by the pseudo-second-order kinetic and the modified Langmuir isotherm models. Overall, due to the synergistic galvanic cell effect of nZVI/Sn nanoparticles and full coverage of active sites by Sn layer, Talc-nZVI/6Sn was utilized as a promising nanocomposite for fast and highly efficient Cr(VI) elimination.